Assessment of Levels of Occupational Exposure to Extremely Low Frequency Electric and Magnetic Fields in Data Centres in Greater Accra Region-Ghana. - Kalognia , J. (University of Ghana, 2016)
Data centres use a lot of power, consumed by two main usages: power required to run the actual equipment and power required to cool the equipment. Usage of electricity results in the production of electric and magnetic fields (EMF). Even though electricity is useful in human lives, there have been reported cases of adverse health effects from EMF generated from its use. Because the use of electricity is ubiquitous and plays a vital role in society’s economy, the possibility of harm from EMF to electric utility customers and workers deserves attention.The Electric and Magnetic fields for workers in data center in the Greater Accra Region have been assessed. The fundamental objective was to determine the levels of the electric and magnetic fields and to assess the extent of exposure of workers in the data centre to these fields. The results obtained for the electric field intensities in the data centre ranged from 6.03E-03 ± 7.54E-04 kVm-1 to 2.33E-04 ± 8.82E-05 kVm-1.The results obtained for the resultant field strength in the data centre ranged from 3.12E-01± 8.77E-03 μT to 6.57E-02 ± 7.38E-03 μT. The results obtained for the magnetic flux density ranged from 3.9E-07 ± 8.77E-03 μT to 7.27E-08 ± 7.31E-03 μT. The results obtained for the induced current density ranged from 2.37E-06 ± 1.50E-02 mA/m2 to 2.46E-07 ± 9.99E-03 mA/m2. Data obtained are below the basic restrictions for induced current density and reference levels for electric field and magnetic flux density set by the International Commission on Non-Ionizing Radiation Protection
Thesis(MPHIL)-University of Ghana, 2016
Keywords: Occupational Exposure; Frequency Electric; Magnetic Fields; Greater Accra Region-Ghana.